Income Stratification in Russia: What do Different Approaches Demonstrate? - Mareeva, Svetlana V.; Lezhnina, Yulia P. (Studies of Transition States and Societies, 2019)
This paper provides empirical analysis of income stratification in contemporary Russian society and its dynamics in recent decades. The paper analyses in detail different approaches (absolute and relative) to defining income groups. It is shown that the most widely used thresholds of the absolute approach cannot be efficiently applied to contemporary Russian society, as they fail to define the subgroups within the population, while relative approach, based on the median income as the social standard of living, appears more effective for income stratification in Russia. A specific income stratification scale is suggested. Its application shows that middle-income groups currently dominate in income structure, however, the incomes of their representatives are not high in absolute terms and their living standards are quite modest. Income stratification in Russia has been noticeably transformed over the last 20 years – the middle-income group has been growing while the low income and high-income groups’ shares have been declining. The proposed scale implies possibilities for structural adjustments such as regional- and settlement-specific disparities in income distribution; it can be easily replicated and allows broad potential for future research, including international comparisons of income stratification in societies undergoing transitional processes.